2013
DOI: 10.1007/s11357-013-9527-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life of liver transplant recipients beyond 60 years of age

Abstract: Due to ameliorated surgery as well as better immunosuppression, the recipient age after liver transplantation has been extended over the past years. This study aimed to investigate the health related quality of life after liver transplantation in recipients beyond 60 years of age. The SF-36 was used to evaluate the recipients' health-related quality of life as standardized tool. It comprises 36 items that are attributed to 8 subscales attributed to 2 components: the physical component score and the mental comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…While quality of life improves after transplant, participants of the present study described ongoing issues associated with mental health and emotional resilience that may impact on health‐related decision making . Unique emotional stressors such as survivor guilt and post‐traumatic stress are recognised in organ transplant recipients .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While quality of life improves after transplant, participants of the present study described ongoing issues associated with mental health and emotional resilience that may impact on health‐related decision making . Unique emotional stressors such as survivor guilt and post‐traumatic stress are recognised in organ transplant recipients .…”
Section: Discussionmentioning
confidence: 89%
“…While quality of life improves after transplant, participants of the present study described ongoing issues associated with mental health and emotional resilience that may impact on health-related decision making. 18 Unique emotional stressors such as survivor guilt and post-traumatic stress are recognised in organ transplant recipients. [19][20][21][22] Study participants indicated that before they could address their diet and exercise needs, they needed better strategies to cope with the insecurity and uncertainty associated with survival; and also needed the physical and emotional resources to deal with their current medical issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus regarding the optimal patient selection process in this population and the costeffectiveness of transplanting older patients as opposed to younger patients has not been addressed. Moreover, quality of life, one of the secondary goals of transplantation, has not been sufficiently studied in older recipients [61]. The place of retransplantation in elderly patients also remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Lately, Health-Related Quality of Life (HRQoL) has gained prominence as a tool to assess the impact of chronic diseases and their treatments on the perception of health and patient well-being (4,(9)(10) . For this purpose, Short Form 36 (SF-36), a generic instrument, and Chronic Liver Disease Questionnaire (CLDQ), which is specifically for HRQoL analysis in patients with chronic liver disease, have been used (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that untreated patients with chronic hepatitis C and those undergoing antiviral therapy with pegylated interferon (PEG-IFN) and ribavirin present significant diminished quality of life indices (4,(9)(10)(12)(13) . However, in Brazil there is the perspective of providing more effective drugs and with fewer adverse events, and triple therapy with telaprevir will possibly remain as a therapeutic option.…”
Section: Introductionmentioning
confidence: 99%